Determinants of Drug-Resistant Tuberculosis in Southern Ethiopia: A Case–Control Study - Biru D; Woldesemayat EM (Infection and Drug Resistance, 2020)
Daniel Biru,1 Endrias Markos Woldesemayat2 1UNICEF Ethiopia, Addis Ababa, Ethiopia; 2Hawassa University, College of Medicine and Health Sciences, School of Public Health, Hawassa, EthiopiaCorrespondence: Endrias Markos WoldesemayatHawassa University, School of Public Health, Hawassa, EthiopiaTel +25192304840Email endromark@yahoo.comBackground: In most developing countries, including in Ethiopia, the magnitude and risk factors of drug-resistant tuberculosis (DR-TB) are expected to be high. However, this is not well reported because of lack of laboratory facilities, poor surveillance system and limited reporting. The aim of this study was to determine the risk factors of DR-TB among TB patients in southern Ethiopia.Patients and Methods: Facility-based case–control study was conducted from November 2016 to January 2017 in Sidama Zone and Gurage Zone of the southern Ethiopia region. DR-TB cases were confirmed by drug-susceptibility testing who were on treatment for DR-TB at Yirgalem and Butajira Hospitals. Controls were smear-positive pulmonary tuberculosis (TB) patients who were taking first-line anti-TB medications and sputum smear-negative at the 5th month of commencing TB treatment. Data were entered and cleaned using EPI-Info version 7 software and analyzed using SPSS version 22 statistical software.Results: A total of 84 cases and 243 controls participated in the study. About 59% (49 cases) and 55% (132 controls) were male. The median (interquartile range) age was 28 (21– 37) years for cases and 27 (25– 33) years for controls. Living in a one-roomed house (adjusted odds ratio [AOR]: 6.8, 95% CI: 1.8– 25.8), history of contact with DR-TB cases (AOR: 6.8, 95% CI: 1.8– 25.3), treatment failure TB cases (AOR: 4.2, 95% CI: 1.1– 15.5) and relapsed TB cases (AOR: 4.8, 95% CI: 1.3– 18.1) were independent factors associated with DR-TB.Conclusion: Providing standardized first-line regimen for new case and retreatment TB cases and practicing basic TB-infection control measures could help to minimize the spread of DR-TB.Keywords: drug resistance, tuberculosis, southern Ethiopia